Serum Metabonomics Reveals Key Metabolites in Different Types of Childhood Short Stature - Chen, Guoyou; Wang, Jinming; Jing, Yisi; Li, Chunxiang; Zhang, Wenyue; Yang, Shuang; Song, Ye; Wang, Xin; Liu, Jincheng; Yu, Dejun; Xu, Zhichun (Frontiers in Pharmacology, 2022)
Graphical Abstract SS, short stature; SDS, standard deviation scores; Control, normal height, n=30; ISS, idiopathic short stature n=31; GHD, short stature caused by growth hormone deficiency, n=29.